A DMAIC approach for process capability improvement an engine crankshaft manufacturing process - G.V.S.S. Sharma; P. Srinivasa Rao (Journal of Industrial Engineering International, 2014)
The define-measure-analyze-improve-control (DMAIC) approach is a five-strata approach, namely DMAIC. This approach is the scientific approach for reducing the deviations and improving the capability levels of the manufacturing processes. The present work elaborates on DMAIC approach applied in reducing the process variations of the stub-end-hole boring operation of the manufacture of crankshaft. This statistical process control study starts with selection of the critical-to-quality (CTQ) characteristic in the define stratum. The next stratum constitutes the collection of dimensional measurement data of the CTQ characteristic identified. This is followed by the analysis and improvement strata where the various quality control tools like Ishikawa diagram, physical mechanism analysis, failure modes effects analysis and analysis of variance are applied. Finally, the process monitoring charts are deployed at the workplace for regular monitoring and control of the concerned CTQ characteristic. By adopting DMAIC approach, standard deviation is reduced from 0.003 to 0.002. The process potential capability index (CP) values improved from 1.29 to 2.02 and the process performance capability index (CPK) values improved from 0.32 to 1.45, respectively.
Keywords: 650; Critical to quality (CTQ) characteristic; Cause and effect diagram; Statistical process control (SPC); Process monitoring charts (PMC); Failure modes and effects analysis (FMEA); Analysis of variance (ANOVA); Physical mechanism (PM) analysis